Design and Fabrication of Crucible Furnaces by using Black Smithy Setup - S.S. Bhandari; S.B. Badadal; V.G. Kinagi; H.S. Tuljapurkar; Prof. S.H. Bansode (International Journal of Engineering and Management Research, 2018)
The main aim was, to design Pit Furnace from the setup of black smithy. As the Smithy setup was not in use so it is converted into Pit Furnace setup. The purpose of using Pit Furnace is to melt nonferrous material. The Nonferrous materials such as Aluminum, Aluminum alloy, Copper, Brass, etc. The Aluminum has less melting point (680ᵒ C, 1218ᵒF) and cheaper than other. The thermal efficiency of furnace is 13.72% which is obtained by melting 2 kg of Aluminum for 75 minutes. Normally thermal of pit furnace is between 4-19%. The blower is used to supply the air into the furnace chamber to burn the coal. For melting the Aluminum, Crucible should sustain higher temperature so Graphite Crucible is used. This Crucible has thinner wall and have more refractory properties.